2006
DOI: 10.1002/chem.200601017
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of 2‐Aryl‐3‐vinyl‐2,3‐dihydrobenzo[b]furans through a Sakurai Reaction: A Mechanistic Proposal

Abstract: The condensation of 2,3-dihydrobenzoxasilepins with aromatic aldehydes in the presence of boron trifluoride to form 2,3-dihydrobenzofurans shows a level of diastereoselection which is a function of the electronic nature of the aldehyde and the polarity of the solvent. The study of the mechanism of the reaction demonstrated that it proceeds through a ring-opened allylfluorosilane, which is stable enough to be isolated and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Finally, we turned our attention to the synthetic utility of products obtained via this novel silyl methyl Heck reaction (Scheme 3 ). 16 Thus, ring opening of silyloxycycle 2a with MeLi, produced 11 in 70% yield. Its subsequent intramolecular Hosomi–Sakurai reaction with 1,1-dimethoxycyclohexane generated spiro benzofuran 12 in excellent yield (Scheme 3 , a).…”
mentioning
confidence: 99%
“…Finally, we turned our attention to the synthetic utility of products obtained via this novel silyl methyl Heck reaction (Scheme 3 ). 16 Thus, ring opening of silyloxycycle 2a with MeLi, produced 11 in 70% yield. Its subsequent intramolecular Hosomi–Sakurai reaction with 1,1-dimethoxycyclohexane generated spiro benzofuran 12 in excellent yield (Scheme 3 , a).…”
mentioning
confidence: 99%
“…We had previously observed [4] that the treatment of the seven membered cyclic allylsiloxane 2,3-dihydro-2,2-dimethylbenzo [ f ][1,2]oxasilepine with boron trifluoride yielded a ring-opened fluorinated derivative. This derivative was able to perform the condensation with aromatic aldehydes to generate the dihydrobenzofuran final products in the presence of a second equivalent of BF 3 ·Et 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study whether the electronic nature of the aldehyde had any influence on the diastereochemical outcome of the reaction, as observed before with the benzoxasilepines, [4] a selection of benzaldehydes with strongly (OMe) or weakly (OPiv) electron donating groups in orto, meta and para positions were assayed (table 1). Under the same experimental conditions used for the preparation of dihydrobenzofurans, the reaction is never diastereospecific, as cis/trans mixtures are always observed, the trans isomer being the major one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-Ray diffraction confirmed the relative stereochemistry of both final products (119 cis and trans). A detailed study of the mechanism of the reaction [105] has demonstrated that it proceeds through a ring-opened allylfluorosilane, which is stable enough to be isolated and characterized.…”
Section: Sakurai-metathesis Routementioning
confidence: 99%